Exploring Fear and Imagination: A Statement of Practice for “Parade Lorong Kosambi” - Bastari, Rendy Pandita (Mudra Jurnal Seni Budaya, 2026)
This statement of practice addresses not merely as a representational theme in visual art, but as a methodological catalyst that shapes artistic perception, decision-making, and meaning-making. The practice-based research explores how fear acts as an experiential and affective condition within the creative process, supporting observation, visual intervention, and material articulation. Using a combination of photography and drawing, the artwork “Parade Lorong Kosambi” juxtaposes photographic realism with drawn imaginary figures to see how imaginative intrusion disrupts the stability of everyday spaces. This study is grounded in a theoretical perspective on memetic transmission, drawing from Richard Dawkins and Richard Brodie to understand fear-related imagery as culturally circulating units, alongside psychoanalytic insights to reflect on fear as an unconscious driver or imaginative projection. These theories serve as interpretive lenses rather than explanatory models, supporting reflective decision-making throughout the practice-led process. The creative methodology involves site-specific observation, photographic documentation of urban locations, visual experimentation through culturally inspired sketching, and material realization using mixed media techniques. Rather than empirically analyzing audience reception, this statement of practice focuses on articulating how fear operates internally within artistic processes and manifests through visual and material strategies. This study contributes to contemporary art discourse by positioning fear as a source of experiential knowledge production within practice-led research. By framing artistic creation as a methodological inquiry into affection and imagination, the work demonstrates how fear can act as a legitimate epistemic force in artistic research, without relying on audience-based evaluation.